1996
DOI: 10.1680/adcr.1996.8.30.47
|View full text |Cite
|
Sign up to set email alerts
|

An accelerated carbonation procedure for studies on concrete

Abstract: Carbonation of the concrete leading to reduced alkalinity around the steel is one of the main reasons for the corrosion of reinforced concrete. Studies of carbonation-induced corrosion and of rehabilitation methods, such as electrochemical re-alkalization, require the convenient preparation of realistically large specimens of carbonated concrete in a sufficiently short time. This paper describes a rapid method of preparing carbonated concrete by exposing concrete, which has been dried to an internal relative h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…1,2 A well-known phenomenon associated with cement-based materials placed in natural environmental locations is the carbonation that occurs naturally over numerous years owing to the reaction with atmospheric CO 2 . 3 In the case of steel reinforced concrete, this is one of the major causes of concrete structure deterioration over time, because the reduction of the pH in the cement paste pore solution due to carbonation enables the corrosion of steel. 4 On the other hand, concrete carbonation allows the use of other nonexpensive reinforcement products, such as glass, plastics, vegetal fibers, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 A well-known phenomenon associated with cement-based materials placed in natural environmental locations is the carbonation that occurs naturally over numerous years owing to the reaction with atmospheric CO 2 . 3 In the case of steel reinforced concrete, this is one of the major causes of concrete structure deterioration over time, because the reduction of the pH in the cement paste pore solution due to carbonation enables the corrosion of steel. 4 On the other hand, concrete carbonation allows the use of other nonexpensive reinforcement products, such as glass, plastics, vegetal fibers, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers suggest that with a high concentration of CO 2 , the porosity of artificially carbonated concrete is greater than that obtained by natural exposure. However, this is controversial, as other studies have shown that even with 100% CO 2 overpressure, the same microstructure occurs as in natural carbonation [47]. All the buildings studied are located in natural and/or urban environments in areas with little traffic and adequately ventilated; only three of the buildings had basements for parking or vehicle traffic, but in all cases, they were well ventilated and with minimal occupancy.…”
Section: Medium Humidity Iib Corrosion Not Caused By Chloridesmentioning
confidence: 90%
“…It was found that 100% of CO2 under increased pressure produce the same microstructure as natural carbonation (Al-Kadhimi et al, 1996). Some codes have estimated carbonation induced corrosion initiation as shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%